2007
DOI: 10.1097/id.0b013e318159cad3
|View full text |Cite
|
Sign up to set email alerts
|

Salivary pH in Edentulous Patients Before and After Wearing Conventional Dentures and Implant Overdentures: A Clinical Study

Abstract: Within the limitations of this study, changes of salivary pH were found after the insertion of conventional dentures and dentures supported by implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Previous investigations had conflicting conclusions with respect to changes in saliva composition after the insertion of new dentures. Bhat et al [ 7 ] found decreased pH salivary levels, whereas Nikolopoulou and Tzortzopoulou [ 9 ] observed higher pH values 15 days after the insertion of either conventional or implant-supported dentures. In our study, there were no significant differences of pH throughout the period under evaluation ( p = 0.172) and this finding is in agreement with Mäkilä [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations had conflicting conclusions with respect to changes in saliva composition after the insertion of new dentures. Bhat et al [ 7 ] found decreased pH salivary levels, whereas Nikolopoulou and Tzortzopoulou [ 9 ] observed higher pH values 15 days after the insertion of either conventional or implant-supported dentures. In our study, there were no significant differences of pH throughout the period under evaluation ( p = 0.172) and this finding is in agreement with Mäkilä [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the first days after insertion of new dentures, sore spots or injured mucosa are commonly observed. Some studies report changes in saliva composition during this period, particularly the concentration of acid uric and pH levels [ 8 , 9 ]. However, it is still unclear if these changes have an impact on the patient's adaptation to the denture and which salivary components play a relevant role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that mean pH of saliva before denture insertion was 6.7 and after denture insertion was 5.1. Nikoloupoulo et al [11] determined changes of pH of resting saliva before and after prosthetic treatment in implant denture wearers. The study sample comprised 2 groups of edentulous patients, ranging in age from 50 to 80, who had not worn complete dentures in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when more mastication was needed, significant changes have been observed in the salivary flow rate with consequent changes in amylase and protein concentration, as well as an increase of pH values respectively [21]. In addition to that, another study reported a statistical significance of pH values before and after the CDs insertion [22]. Others, however, have not found significant changes in pH values [4,23].…”
Section: Disscusionmentioning
confidence: 99%